PENGEMBANGAN PERALATAN PENYULINGAN MINYAK ATSIRI JERUK PURUT (Citrus hystrix D.C) MENGGUNAKAN SISTEM UAP (Development of Lime (Citrus hystrix D.C) Essential Oil Refining Equipment Using Steam System) - Syarifuddin, Syarifuddin (Jurnal Hasil Penelitian Industri, 2016)
The extraction of essential oils can be done several ways such as: boiling systems, steamsystems, combined of steam systems and extraction with organic solvents. In an industrial scale extraction ofessential oils from the leaves of lime is more efficient by steam distillation system. In this research, there arethree methods to develop refining equipment, first: Use of sawdust as a substitute for firewood by usingcylindrical stove so as to save costs, the need for cost sawdust 0,38USD/ distillation cycle, second reduction thegoose neck can increase the pressure on the boiler so that distillation proses can be shortened to 2 hours andthe third use of double condenser cooling causes the distillate is perfect. Equipment Specifications of kettleasfollows: 1000 mm in high, 500 mm in diameter, raw materials capacity 10 kg/distillation. Handling rawmaterials before refining also affect the yield. Lime essential oil using this equipment has a yield of 0.67% to0.98%. Essential oils are produced having physical properties include solubility in alcohol 1:1, transparent(colorless), refractive index of 1.3600â1.3786 and density 0,8543 â 0,8614 g/cc. Chemical constituents of limeoil in the GCMS analysis comprise of : Linalool 4.19%, I-Phellandrene 4.30%, alpha-Fenchene 2.22%,geranyl acetate 4.10%, Citronella 47.98%, beta-Citronellol 48.58%, Cytronellyl acetate 9.18%, tran-Caryopyllene 1.68%. The results on the chemical components examination shows that there are about 23 activecomponents in which the percent cumulative amount is still small. The quality of the lime essential oil is highlydependent on the number of citronella content.